2009
DOI: 10.1007/s12640-009-9125-y
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Enhances Astroglia and Microglia Reactivity Induced by 3,4-Methylenedioxymethamphetamine (‘Ecstasy’) in Mouse Brain

Abstract: Several reports suggest that 3,4-methylenedioxymethamphetamine (MDMA) induces neurotoxic effects and gliosis. Since recreational use of MDMA is often associated with caffeinated beverages, we investigated whether caffeine interferes with MDMA-induced astroglia and microglia activation, thus facilitating its neurotoxicity. MDMA (4 x 20 mg/kg) was acutely administered to mice alone or in combination with caffeine (10 mg/kg). CD11b and GFAP immunoreactivity were evaluated as markers of microglia and astroglia act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 13 publications
4
48
0
Order By: Relevance
“…By contrast, oleoylethanolamide, an endocannabinoid that reduce L-DOPA-induced dyskinesias (Gonzalez-Aparicio and Moratalla, 2014) also reduces cognitive deficits and THinduced by MDMA (Plaza-Zabala et al, 2010). Interestingly, these results are in line with earlier evidence that demonstrates the existence of noxious interactions between MDMA and other substances that act on the CNS such as ethanol (Izco et al, 2010;Ros-Simό et al, 2012) or caffeine (Khairnar et al, 2010). A recent study revealed that the coadministration of DPCPX, an A 1 receptor antagonist, amplifies the effects of MDMA on both microglial and astroglial activation in the striatum, suggesting that the A 1 receptor could be the adenosine receptor subtype most involved in the exacerbation of MDMA-induced gliosis by caffeine (Khairnar et al, 2014).…”
Section: 1micesupporting
confidence: 91%
See 1 more Smart Citation
“…By contrast, oleoylethanolamide, an endocannabinoid that reduce L-DOPA-induced dyskinesias (Gonzalez-Aparicio and Moratalla, 2014) also reduces cognitive deficits and THinduced by MDMA (Plaza-Zabala et al, 2010). Interestingly, these results are in line with earlier evidence that demonstrates the existence of noxious interactions between MDMA and other substances that act on the CNS such as ethanol (Izco et al, 2010;Ros-Simό et al, 2012) or caffeine (Khairnar et al, 2010). A recent study revealed that the coadministration of DPCPX, an A 1 receptor antagonist, amplifies the effects of MDMA on both microglial and astroglial activation in the striatum, suggesting that the A 1 receptor could be the adenosine receptor subtype most involved in the exacerbation of MDMA-induced gliosis by caffeine (Khairnar et al, 2014).…”
Section: 1micesupporting
confidence: 91%
“…Moreover, independent studies have shown that the toxic and inflammatory effects of MDMA are exacerbated by its concurrent administration with other psychoactive substances, such as caffeine or ethanol (Hernandez-Rabaza et al, 2010;Khairnar et al, 2010;Frau et al, 2013a) and, at the same time, MDMA worsens neuroinflammation produced by toxins inducing PD, such as MPTP (Costa et al, 2013).…”
Section: 2neuroinflammationmentioning
confidence: 99%
“…10,11 Besides interest in this interaction with regard to psychostimulant properties, recent studies from our and other groups have indicated that amphetamine-related psychostimulants exert toxic and proinflammatory effects on the brain, and that caffeine may amplify these effects. [12][13][14] This adds to the evidence showing that caffeine exacerbates the noxious effects of amphetaminerelated psychostimulants on peripheral organs, 15 and suggests that combined consumption of caffeine and psychostimulants may pose a health risk, which may even affect the brain.…”
mentioning
confidence: 90%
“…42 In addition to the psychostimulant effects of caffeine, evidence is accumulating to indicate that the central interactions between caffeine and amphetaminerelated drugs are not only relevant to drug abuse, but can be crucial in exacerbating amphetamine-mediated neurotoxic and neuroinflammatory effects when these substances are consumed together. 13,43 …”
Section: Psychostimulant Effectsmentioning
confidence: 99%
“…[67][68][69] However, caffeine, when given acutely, potentiates the increase of GFAP in the Str and enhances the acute toxicity and lethalness of 3,4-methylenedioxymethamphetamine (MDMA). 70,71 Moreover, it has been demonstrated that other psychostimulant drugs affect the expression of GFAP and induce strong changes in the astrocyte proliferation rate (cocaine and MDMA exposure), [71][72][73] generating many reactive species enabling neurodegeneration. 73,74 Besides the double effect of caffeine on glial cells, up-or downregulation, it is postulated that an upregulation of adenosine receptors takes place after chronic caffeine exposure.…”
Section: Ballesteros-yá ñ Ez Et Almentioning
confidence: 99%